The Role of the Surau Education System for Elementary School Children - Anwar, Miftahul; Wakhid, Muhammad Umar; Warisno, Andi; Anshori, Afif; Andari, Anan (Universitas Pahlawan Tuanku Tambusai, 2023)
Due to its role as an educational facility throughout the early stages of Islam's development in Indonesia, Surau demonstrates institutional existence in educating the country's youth in addition to historical relevance. This study aims to describe the advantages of the surau educational system for elementary school children. Techniques from qualitative and historical research are used in this type of study. Accumulating knowledge through time by studying literature, such as books, magazines, and rules controlling surau educational institutions. Heuristics were used to acquire sources, source critique was used to validate and select material, interpretation was used to interpret historical facts, and historiography stages were used to put the information together into a chronology. The study's conclusions indicate that the following functions of surau education are important: (1) fostering moral and ethical qualities in children; (2) fostering an understanding of Islamic teachings; (3) enhancing moral and ethical qualities; (4) fostering an understanding of Islamic teachings; and (5) fostering the capacity to worship, study, and gather and organize. In light of the fact that the surau education approach influences how kids form their religious identities at an early age, it was decided that it should be incorporated into the contemporary educational system.